2021
DOI: 10.3389/fitd.2021.719369
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Methodological Considerations on Vaccine Candidates for Human Schistosomiasis

Abstract: Schistosomiasis remains a neglected tropical disease of major public health concern with high levels of morbidity in various parts of the world. Although considerable efforts in implementing mass drug administration programs utilizing praziquantel have been deployed, schistosomiasis is still not contained. A vaccine may therefore be an essential part of multifaceted prevention control efforts. In the 1990s, a joint United Nations committee promoting parasite vaccines shortlisted promising candidates including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 179 publications
(319 reference statements)
0
11
0
Order By: Relevance
“…Given the recent advances in schistosomal vaccine candidates [8] and the lack of consensus in standardized parameters assessing protection in humans impeded by the lack of diagnostic tools as per WHO's ASSURED criteria suggests to consider expanding isothermal detection techniques to the field of vaccinology. In summary, LAMP and RPA reached species-dependent sensitivity up to 100% and detection in the femtogram range within clinical applications for diagnosing human schistosomiasis; hybridale DNA was found in nanogram amounts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the recent advances in schistosomal vaccine candidates [8] and the lack of consensus in standardized parameters assessing protection in humans impeded by the lack of diagnostic tools as per WHO's ASSURED criteria suggests to consider expanding isothermal detection techniques to the field of vaccinology. In summary, LAMP and RPA reached species-dependent sensitivity up to 100% and detection in the femtogram range within clinical applications for diagnosing human schistosomiasis; hybridale DNA was found in nanogram amounts.…”
Section: Discussionmentioning
confidence: 99%
“…S. haematobium causes urogenital pathologies such as dysuria and hematuria and so called female genital schistosomiasis (FGS) if eggs are deposited in the female genitalia [6]. FGS impairs fertility, e.g., ectopic pregnancy and miscarriage, and susceptibility to viruses, e.g., human immunodeficiency virus [7] and papillomavirus, and progressing to malignancies augmented by calcification, e.g., squamous cell carcinomas and sandy patches [8][9][10][11][12]. Ectopic excess egg deposition or erroneous migrating adult worms within the central nervous Acute schistosomiasis or Katayama fever seen among individuals without past parasitic exposure presents as debilitating febrile illness coupled with, e.g., headache, myalgia, fatigue, diarrheal, as well as respiratory symptoms, and hepato-and/or splenomegaly following an incubation period of up to 10-12 weeks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, Sm-p80-specific IgE antibodies are not detectable in sera from individuals living in S. mansoni endemic areas [55,56], thereby removing the potential risk of vaccine-induced hypersensitivity reactions. A phase 1a clinical trial using Sm-p80 formulated in GLA-SE (SchistoShield ® , Seattle, DC, USA) has commenced in infectionnaïve adults in the United States, and this will be followed by a Phase 1b dose-escalation trial among African adults, with a planned future age de-escalation study in school-aged children [57].…”
Section: Schistosoma Mansoni Calpain (Sm-p80)mentioning
confidence: 99%
“…In schistosomes, these enzymes (28GSTs) play critical roles in host immune modulation during infection, including annulling the capacity of epidermal Langerhans cells to move to the draining lymph nodes [63], the binding of testosterone and the detoxification of xenobiotic compounds [64,65]. Since its characterization in the late 1990s, data from several efficacy studies using the Sh28GST vaccine in murine and nonhuman primate models of S. haematobium infection and disease showed protective immunity following cercarial challenge with profound effects on tissue egg pathology and excretion [35,57]. An initial Phase 1 study assessed the safety, tolerability and immunogenicity of recombinant Sh28GST (rSh28GST) adsorbed to Alhydrogel (Bilhrvax ® Lille, France) in healthy Caucasian adults, and showed that the vaccine was well-tolerated and elicited a strong Th2-biased immune response [66].…”
Section: Schistosoma Haematobium 28-kda Glutathione S-transferases (S...mentioning
confidence: 99%